2022
DOI: 10.1093/cid/ciac605
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes in a Randomized Controlled Trial Comparing Point-of-Care With Standard Human Immunodeficiency Virus (HIV) Viral Load Monitoring in Nigeria

Abstract: Background Point-of-care (POC) viral load (VL) tests provide results within hours, enabling same-day treatment interventions. We assessed treatment outcomes with POC versus standard-of-care (SOC) VL monitoring. Methods We implemented a randomized controlled trial at an urban and rural hospital in Nigeria. Participants initiating antiretroviral therapy (ART) were randomized 1:1 for monitoring via the POC Cepheid Xpert® or SOC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…By having closer POC DRT facilities to the spoke facilities than the national laboratory, this issue of batching delay is overcome by a network that includes POC DRT hubs. Since direct data about the impact of POC DRT testing on results utilisation have not been studied, parallels with POC VL testing may be useful: although POC VL testing has not necessarily consistently improved viral suppression,21 46–48 improved turnaround times are highly motivating for providers and patients49 and result utilisation appears to improve as well 20 47 50…”
Section: Discussionmentioning
confidence: 99%
“…By having closer POC DRT facilities to the spoke facilities than the national laboratory, this issue of batching delay is overcome by a network that includes POC DRT hubs. Since direct data about the impact of POC DRT testing on results utilisation have not been studied, parallels with POC VL testing may be useful: although POC VL testing has not necessarily consistently improved viral suppression,21 46–48 improved turnaround times are highly motivating for providers and patients49 and result utilisation appears to improve as well 20 47 50…”
Section: Discussionmentioning
confidence: 99%
“… 21 In this study, all participants were on first-line efavirenz-based regimens, there were few participants with viral failure (16 of 390, 4.1%), and the research team conducted clinical management in the intervention arm, meaning it is difficult to determine the contribution of point-of-care testing within the overall implementation strategy. Trials among children in Kenya, 17 adolescents in Haiti, 18 and adults in Nigeria 19 , 20 found that point-of-care VL testing improved time to receipt of VL results by 2, 4, and 20 weeks, respectively, with improved switching to second-line ART. However, none of these trials found a clear impact on viral suppression.…”
Section: Discussionmentioning
confidence: 99%
“…To date, 2 point-of-care assays have been approved as accurate by the WHO for use in LMICs 13,14 and have been evaluated in our setting. 15,16 Clinical trials of these assays among children, 17 adolescents, 18 and adults [19][20][21] have demonstrated shorter turnaround times, but effects on clinical outcomes have been mixed.…”
Section: Introductionmentioning
confidence: 99%
“…A South African randomized controlled trial compared 3monthly POC VL testing to 6-monthly SOC laboratory-based VL testing among postpartum women living with HIV on firstline ART, and found no significant difference in VL suppression rates [23]. Similarly, a study among Nigerian adults initiating ART reported that POC VL monitoring did not improve 12-month VS, but it did improve retention and VS documentation and was favoured by the majority of patients and healthcare workers [24]. Other studies demonstrated some benefits to POC VL.…”
Section: Discussionmentioning
confidence: 99%